2015
DOI: 10.1242/jcs.167981
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanin-3 is an organizer of the multi-subunit Nogo-A signaling complex

Abstract: To ensure precision and specificity of ligand-receptor-induced signaling, co-receptors and modulatory factors play important roles. The membrane-bound ligand Nogo-A (an isoform encoded by RTN4) induces inhibition of neurite outgrowth, cell spreading, adhesion and migration through multi-subunit receptor complexes. Here, we identified the four-transmembrane-spanning protein tetraspanin-3 (TSPAN3) as a new modulatory co-receptor for the Nogo-A inhibitory domain Nogo-A-Δ20. Single-molecule tracking showed that TS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 93 publications
(138 reference statements)
0
10
0
Order By: Relevance
“…This analysis yielded several insights: i) the intracellular domains of TSPAN12 are not predominantly important for function, ii) the large extracellular loop of TSPAN12 is required for association with the NDP receptor complex via FZD4, and iii) TSPAN12 incorporation into the NDP receptor complex is required for TSPAN12 function. In light of a recent study reporting that TSPAN3 modulates NOGO-A/S1PR2 GPCR signaling (Thiede-Stan et al, 2015), it appears that tetraspanin activity and GPCR receptor signaling intersect in multiple biological contexts.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis yielded several insights: i) the intracellular domains of TSPAN12 are not predominantly important for function, ii) the large extracellular loop of TSPAN12 is required for association with the NDP receptor complex via FZD4, and iii) TSPAN12 incorporation into the NDP receptor complex is required for TSPAN12 function. In light of a recent study reporting that TSPAN3 modulates NOGO-A/S1PR2 GPCR signaling (Thiede-Stan et al, 2015), it appears that tetraspanin activity and GPCR receptor signaling intersect in multiple biological contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Tetraspanins also modulate intracellular signaling pathways by coordinating ligand-receptor binding at the cell surface. This is exemplified by the observation that tetraspanin 3 promotes binding of the NogoA ligand to the receptor sphingosine-1-phosphate-receptor-2 (S1PR2), which activates an intracellular signaling cascade leading to the inhibition of neurite outgrowth (Thiede-Stan et al, 2015). Most tetraspanins regulate the functions of their partner proteins by modulating their spatiotemporal distribution at the plasma membrane and organizing them together with other functional proteins (e.g., enzymes and substrates) (Odintsova et al, 2003; Haining et al, 2012; Thiede-Stan et al, 2015).…”
Section: Functions Of Tetraspaninsmentioning
confidence: 99%
“…This is exemplified by the observation that tetraspanin 3 promotes binding of the NogoA ligand to the receptor sphingosine-1-phosphate-receptor-2 (S1PR2), which activates an intracellular signaling cascade leading to the inhibition of neurite outgrowth (Thiede-Stan et al, 2015). Most tetraspanins regulate the functions of their partner proteins by modulating their spatiotemporal distribution at the plasma membrane and organizing them together with other functional proteins (e.g., enzymes and substrates) (Odintsova et al, 2003; Haining et al, 2012; Thiede-Stan et al, 2015). Recent studies, demonstrated that the interaction with tetraspanins influences the motility of their partner proteins and their association with other molecules within the plasma membrane (Yang et al, 2012; Mattila et al, 2013; Jouannet et al, 2015).…”
Section: Functions Of Tetraspaninsmentioning
confidence: 99%
“…This receptor was recently identified. In mammals, the GPCR S1PR2 is the signal transducing element of a receptor complex for Nogo‐A delta20 (Kempf et al, ; Thiede‐Stan et al, ). Our in situ hybridization experiments show that zebrafish RGCs express the homologue of S1PR2, as well as S1PR5a which is another member of the family.…”
Section: Discussionmentioning
confidence: 99%